Identify SIF and specify necessary SIL, and other IPLs, as part of PHA/HAZOP – or ‐ why it is not necessary to "boldly go beyond HAZOP and LOPA". Issue 4 (10th November 2016) - Bridges, William G.; Dowell, Arthur M.
Abstract : This article shows how to apply the qualitative definition of IPLs within the setting of a process hazard analysis (PHA) to get most of the gain from Layer of Protection Analysis (LOPA) without doing a LOPA (without using numerical values). The article includes an implementation path to develop PHA leader competencies to guide the qualitative approach. We also show the way we use a PHA team to identify when a SIF is needed and to select the proper target safety integrity level (SIL). This portion of the SIL evaluation and the identification and labeling of the IPLs during the PHA/hazard and operability analysis (HAZOP) does not take any longer than a normal PHA/HAZOP, once the right habits are established. Note that this approach eliminates the need for a separate SIL Evaluation Study to identify the SIFs and select the target SIL. Finally, the article ties together these two specific topics, along with the topic of making risk judgments, to show there is less than 5% need to go beyond HAZOP, and less than 0.01% need to go beyond LOPA. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 349–359, 2016